Effects of Internet Language Related to COVID-19 on Mental Health in College Students: The Mediating Effect of Cognitive Flexibility - Wu, Xingzhe; Wang, Zhi; Zhang, Hongpo; Yuan, Peiming; Yu, Quanlei; Zhou, Zhijin; Zhao, Qingbai (Frontiers in Psychology, 2021)
During the COVID-19 pandemic, Internet language (INL) has influenced daily life extensively. However, the process by which INL influences people’s psychology and behavior is unclear. This study explored the effects of INL on mental health (anxiety and depression). A pilot study was conducted to develop a qualified scale for INL related to COVID-19 (CINL) in college students using an online questionnaire. The CINL scale was found to have two dimensions: frequency and comprehension, as well as good reliability and validity. A formal study explored the mediating effect of cognitive flexibility on the relationship between CINL and mental health. The results showed that CINL positively predicted mental health when it was mediated by cognitive flexibility. These results not only provide a new perspective on understanding the effects of cyber behavior on human mental health from a positive perspective, but also provide practitioners with new insights for interventions on college students’ mental health.